‘Filosofía del no’ en la economía ecológica aplicada a los recursos naturales (REVIBEC - REVISTA IBEROAMERICANA DE ECONOMÍA ECOLÓGICA, 2018)
Ecological economics has generated proposals to analyze the depredation of natural resources and reduce it. This text, however, aims to show that there are elements to affirm that the acceptance of the existence of natural resources that collaborates in such predation and binds the postnormal science to the principles of normal science, which prevents to complete the scientific revolution. But if in pursuit of completing such revolution, the ecological economics denies the intuitive experience of neoliberal economics, one of the tasks would be to analyze the natural resource syntagm and renounce to it.